Quality of Life Among Senior Citizens in Bhutan: Associations With Adverse Life Experiences, Chronic Diseases, Spirituality, and Social Connectedness. (January 2017) - Dorji, Nidup; Dunne, Michael P.; Seib, Charrlotte; Deb, Sibnath
This study explored associations between quality of life (QOL), spirituality, social integration, chronic diseases, and lifetime adversity among people aged 60 years and older in Bhutan. Adults aged 60 to 101 years (n = 337) completed face-to-face interviews. The main measure included the World Health Organization QOL questionnaire and Adverse Childhood Experiences International Questionnaire. The social relationships domain of QOL had the highest mean. Frequent back pain, memory decline, depression, mobility impairment, insomnia, and lung diseases were commonly reported and negatively related to QOL. Compared with women, men reported fewer physical and mental health problems and better QOL. Multivariate analysis revealed that cumulative health problems, psychological distress, and social connectedness contributed significantly to overall QOL. The measure of spirituality was negatively associated with QOL, which is not conclusive and suggests the need for more research especially when the influence of spiritualism is highly visible in the everyday lives of Bhutanese people. The significance of these findings is discussed in relation to care for elderly people in Bhutan.